Industrial Waste Treatment using TiO2 Modified Clay as Adsorbent-Photocatalyst: Mini Review - Kurnia Sri Yunita; Andika Mayansara; Rosmini Rosmini; La Ode Agus Salim (LPPM ISTEK 'Aisyiyah Kendari, 2023)
Every year, the global industrial sector continues to experience rapid development, contributing to economic growth rates, especially in the textile industry. This has led to an increase in the amount of textile dye waste being distributed into the environment. One solution to address the issue of textile dye waste is by modifying clay with TiO2 (TiO2/clay) using degradation-adsorption techniques. In recent decades, the modification of clay minerals has become crucial due to their diverse potential as catalysts, adsorption media, and ion exchange agents. TiO2 serves as a medium for ion insertion (intercalation), which enhances pore and surface area. This study explains the properties of clay, the photocatalytic properties of TiO2, surface characteristics, and the photocatalytic/adsorption method on the TiO2/clay composite. Various types of minerals have been inserted, such as rectorite, montmorillonite, kaolinite, vermiculite, and halloysite, between the layers of clay minerals through different methods and applications. The performance enhancement of tested dyes is carried out by doping metals into the photocatalytic/adsorption material